Divided Cyprus : modernity, history, and an island in conflict - Papadakis, Yiannis; Peristianis, N. (Nicos); Welz, Gisela (New anthropologies of Europe., 2006)
Divided Cyprus brings together the most up-to-date social and cultural research on Cyprus. This small island continues to draw the world's attention as the site of one of the longest-running postcolonial ethnic conflicts, one which has come to play a pivotal role in the politics of the European Union. The contributors to the volume suggest that this conflict offers insight into understanding the relation between "state" and "nation" and the nature of ethnic identity and collectivity